2021
DOI: 10.1186/s41601-021-00189-9
|View full text |Cite
|
Sign up to set email alerts
|

Communication infrastructure for situational awareness enhancement in WAMS with optimal PMU placement

Abstract: Real time monitoring and control of a modern power system has achieved significant development since the incorporation of the phasor measurement unit (PMU). Due to the time-synchronized capabilities, PMU has increased the situational awareness (SA) in a wide area measurement system (WAMS). Operator SA depends on the data pertaining to the real-time health of the grid. This is measured by PMUs and is accessible for data analytics at the data monitoring station referred to as the phasor data concentrator (PDC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…i l and j b are sparse vectors. The primal dual interior point algorithm and sparse description methods [7]…”
Section: Joint State Estimation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…i l and j b are sparse vectors. The primal dual interior point algorithm and sparse description methods [7]…”
Section: Joint State Estimation Modelmentioning
confidence: 99%
“…A quadratic constraint quadratic estimation model based on the SCADA and PMU measurements is proposed to perform robust state NESP-2022 Journal of Physics: Conference Series 2351 (2022) 012011 IOP Publishing doi:10.1088/1742-6596/2351/1/012011 2 estimation [5]. Some scholars have improved the accuracy of DSSE under limited PMUs by studying the optimal placement of PMUs [6][7].…”
Section: Introductionmentioning
confidence: 99%
“…There are several cyber-attacks, such as Distributed Denial of Service (DDoS) and Man-in-The-Middle (MITM) attacks, which can modify the operating data of PMU or damage the PMU operations. Therefore, a novel approach to deploying backup PMU is discussed to maintain the observability and reliability of the interconnected synchrophasor network [33]. The backup allocation of PMU is based on the abnormality characteristics of optimally deployed PMU by including and excluding the effect of ZIB.…”
Section: Impact Of Cyber-attack In Modelling Of Synchrophasor Smart G...mentioning
confidence: 99%
“…From this figure, it can be observed that the main applications in an SG are the energy management systems (EMS), electric vehicles (EVs), microgrids (MGs), smart cities (SCs), home automation (HA), advanced metering infrastructure (AMI), and synchrophasor applications (SPAs) [2]. SG enhances the reliability of power supply and materializes several applications at the cost of increased complexity [3]. In this complex network, at a given instance, there are several entities in the grid that carry out transactions.…”
Section: Introductionmentioning
confidence: 99%
“…SG enhances the reliability of power supply and materializes several applications at the cost of increased complexity [3]. In this complex network, at a given instance, there are several entities in the grid that carry out transactions.…”
Section: Introductionmentioning
confidence: 99%